2022
DOI: 10.5433/1679-0359.2022v43n5p2109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the fungicide strobilurin on forage rye production under different harvesting systems

Abstract: The goal of this study was to evaluate the effects of successive harvests, with or without application of foliar fungicide, on the morphometric characteristics, yield and nutritional value of rye forage harvested at the hard dough grain stage, aiming at silage production. The preventive control of foliar diseases was carried out with the fungicide OrkestraTM SC®, in a single application, at early flowering, for both harvesting systems. The first harvest was conducted at the full vegetative stage and the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In the second harvest, the percentage of stem increased compared to that of leaves, corroborating Meinerz et al (2012), who state that the leaf: stem ratio tends to decrease with the increase and/or advancement of harvests. With the application of pyraclostrobin, the increase in the proportion of leaves corroborates the data found by Silva et al (2022), which showed an increase in leaf area, when pyraclostrobin was applied to rye crops. Fungicide application increased the number of viable leaves (Kalebich et al, 2017), thus improving the leaf: stem ratio.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the second harvest, the percentage of stem increased compared to that of leaves, corroborating Meinerz et al (2012), who state that the leaf: stem ratio tends to decrease with the increase and/or advancement of harvests. With the application of pyraclostrobin, the increase in the proportion of leaves corroborates the data found by Silva et al (2022), which showed an increase in leaf area, when pyraclostrobin was applied to rye crops. Fungicide application increased the number of viable leaves (Kalebich et al, 2017), thus improving the leaf: stem ratio.…”
Section: Discussionsupporting
confidence: 89%
“…Dry matter values were lower in the treatment with pyraclostrobin, probably because it has characteristics that increase water retention within the plant due to reduced stomatal opening (Grossmann et al, 1999). However, Heker et al (2020) and Silva et al (2022) report that the application of pyraclostrobin did not change the dry matter values of plants harvested at the vegetative stage.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations